From Neurology to Methodology and Back An Introduction to Clinical Neuroengineering - Maurits, Natasha; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
In today$1 (Bs hospitals, the gap between technology and medicine constantly needs to be bridged, both by physicians and engineers. By taking a unique clinical neuroengineering approach, From Neurology to Methodology and Back off ers a translational study of neurology and technology, spanning traditionally distinct focuses. The fundamental topics covered range from basic concepts such as sampling and simple statistical measures via Fourier analysis to source localization. Providing clinically relevant context and introduce technical concepts, the neurological diseases presented range from epilepsy, brain tumors and cerebrovascular diseases to tremor, MS and neuromuscular diseases. All topics are presented in a true clinical neuroengineering approach. Each chapter begins with one or more patient cases for inspiration. Each case is then presented to illustrate a working example of a distinct neurodiagnostic technique, and the mathematical and physical principles underlying these techniques are explained. Finally, the author returns to the patient, and examines how the presented technology can help provide a diagnosis for each case. From Neurology to Methodology and Back serves as an upper-undergraduate/graduate level guide for those interested in a translational approach between the fields of medicine and technology in neuroengineering. Neurologists and residents in neurology, medical engineers, medical students, biomedical engineers and students, technical medicine students or students of other interdisciplinary fields will therefore all find this book useful.s
Introduction -- Carpal Tunnel Syndrome, Electroneurography, Electromyography and Statistics -- Tremor, Polymyography and Spectral Analysis -- Epilepsia, Electroencephalography, Filtering and Feature Extraction -- Multiple Sclerosis, Evoked Potentials and Enhancing Signal-to-Noise Ratio -- Cortical Myoclonus, EEG-EMG, Back-Averaging and Coherence Analysis -- Psychogenic Movement Disorders, Bereitschaftspotential and Event-Related Potentials -- Brain Tumor, Pre-Operative Function Localization and Source Localization -- Neuromuscular Diseases, Ultrasound and Image Analysis -- Cerebrovascular Disease, Ultrasound and Hemodynamical Flow Parameters -- Spinal Dysfunction, Transcranial Magnetic Stimulation and Motor Evoked Potentials.
Keywords: Medicine; Neurosciences; Neurology; Biomedicine; Biomedicine general; Neurology; Neurosciences